Kajian Metode Evaluasi Kesesuaian Lahan untuk Kakao di Kabupaten Bantaeng - Anwar Anwar; Muliati Galib; Wahyuni M (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2019)
Land evaluation is an assessment of the potential of land resources. The results of land evaluation will provide information on the best use of it which will lead to expected value of production. This study aimed to determine the level of suitability of the cocoa plantations in Bantaeng Regency using the FAO and Sys methods; make a map of the actual and potential land suitability. The results of the analysis showed that the actual cocoa land suitability of the FAO method was presented in distribution points according to marginal (S3rn) with limiting factor of rooting media and nutrients availability. While the actual land suitability analysis of the cocoa Sys method was not suitable (N1cSf) with climate limiting factors, the soil physical properties and soil fertility. Based on the limiting factors the physical properties of the two methods, there were similarities in effective depth (FAO) and soil depth (Sys), S3 parameters according to FAO and N1 according to Sys. The limiting factor for the soil chemical properties of the two methods was also the same, the availability of S3 (FAO) nutrients, while the (Sys) method was the soil fertility N1.